Pirates, Merchants, Settlers, and Slaves : Colonial America and the Indo-Atlantic World. - McDonald, Kevin P., 1972- (Fletcher Jones Foundation Humanities Imprint., 2015)
"In the late seventeenth and early eighteenth centuries, more than a thousand pirates poured from the Atlantic into the Indian Ocean. There they helped launch an informal trade network that spanned the Atlantic and Indian Ocean worlds, connecting the North American colonies with the rich markets of the East Indies. Rather than conducting their commerce through chartered companies based in London or Lisbon, colonial merchants in New York entered into an alliance with Euro-American pirates based in Madagascar. Pirates, merchants, settlers, and slaves explores the resulting global trade network located on the bperipheries of world empires and shows the illicit ways American colonists met the consumer demand for slaves and East India goods. The book reveals that pirates played a significant yet misunderstood role in this period and that seafaring slaves were both commodities and essential components in the Indo-Atlantic maritime networks."--Provided by publisher.